Unconscious Structures in the Japanese Folk Tales Hebi No Yomeiri, Hato No Koukou, Tsuru No On’gaeshi, and Tanabata - Robi Wibowo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This article analyzes four Japanese folk tales (myths) using the unconscious structures approach pioneered by Lévi-Strauss to uncover the connections between these myths and the unconscious structures of the society that holds them. The first step is to find the outer structures of the four analyzed myths and analyze them both synchronically and diachronically to find their component mythemes. The second step is to analyze and identify the inner structures of these mythemes. These inner structures can then be refined into a series of binary oppositions. Subsequently, the structures of these myths are connected to ethnographic data of the Japanese people, thus producing transformations which indicate the unconscious structures under investigatie. This analysis shows there are oppositional logics centered around the concept of duty, a fundamental part of Japanese morality – opposition between “willingness” and “reluctance” as well as between “gimu”and “giri”. These oppositional logics are the unconscious structures of their reason for duty, rooted in the concept of “obeisance”.